{N,N-Bis[2-(diphenylphosphanyl)ethyl]aniline}(η(2)-dibenzylideneacetone)palladium(0) - Keskin, Seyma Gören (International Union of Crystallography, 2011)
In the title complex, [Pd(C(34)H(33)NP(2))(C(17)H(14)O)], the Pd(0) atom is coordinated in a trigonal planar geometry formed by two P atoms of a bis[(diphenylphosphino)ethyl]aniline ligand and a C=C (η(2)) bond involving the C atoms that are in the α,β positions relative to the central ketone of the dibenzylideneacetone ligand.